A Case of Diabetic Ketoacidosis Presenting with Hypernatremia, Hyperosmolarity, and Altered Sensorium. (16th July 2018) - Kumar, Vinod; Nanavati, Sushant M.; Melki, Gabriel; Upadhyaya, Mira; Dhillon, Raman; Gibiezaite, Sandra; Michael, Patrick; Singhal, Monisha
Abstract : Diabetic Ketoacidosis commonly presents with hyponatremia, but hypernatremia is a rare entity. We report a unique case of a 50-year-old woman admitted with altered sensorium with blood glucose 979 milligrams/deciliter, serum osmolarity 363 mOsm/kilograms, and serum sodium 144 milliequivalents/liter. Patient was given initial bolus of isotonic saline and continued on half isotonic saline for correction of hypernatremia along with insulin infusion therapy. Patient was successfully treated with intravenous fluids, insulin infusion, and the altered sensorium was resolved without any sequelae. This case illustrates a teaching point in the use of intravenous fluids for the treatment of Diabetic Ketoacidosis with hypernatremia.